THE ECONOMIC COSTS OF YOUTH UNEMPLOYMENT IN NORTH MACEDONIA - Mamuchevska, Daniela; Trpeski, Predrag; Gunter, Merdzan (Institute of Knowledge Management, 2022)
Youth unemployment is an issue that seriously concerns many countries, both developed and developing countries. Youth unemployment rates (as % total labor force ages 15-24) in North Macedonia is (36.9% in 2020), and despite recent improvements in labor market indicators, it has remined relatively high in comparison with the rest of Western Balkans countries (35.08% in 2020) and the EU average level (14.4% in 2019). High youth unemployment and inactivity provoke many negative consequences both for young individuals and for the whole society. For young people the long-term unemployment status negatively affects their prospects to find decent jobs, increase the social exclusion by losing of their skills and qualifications; and have negative impact on health status. For society the costs of youth unemployment and inactivity include higher fiscal costs due to unemployment benefits, forgone earnings, and taxes; increase poverty and income inequality; and reduce the aggregate consumption. Also, the high rates of youth unemployment provoke migration process of young population from a country, which may jeopardize the prospects of country’s future economic growth. Facing with the problem of high youth unemployment rates, in the several past years, North Macedonia have proposed and implemented different policies and measures to decrease the youth unemployment rates (National Youth Strategy 2016-2025, Youth Employment Action Plan 2016-2020, Youth Guarantee plan (2020-2022, and etc). In that context, North Macedonia was the first country, outside from the European Union, that has implemented the Youth Guarantee program in 2018, as a pilot project. And since 2019, the Youth Guarantee program has become a regular part of the youth labour policy. All these policies put the focus on improving education and working skills because it is expected that education increases chances for employment of young people, especially for those that belong to NEET category. Output and unemployment commonly move together. There are a number of empirical research with focus on the link between the output change and change in the unemployment. The most prominent one is the empirical research of Okun (1962) who defined the relationship between the change in the unemployment rate and the change of output growth rate. Therefore, the concept of the Okun’s Law is often used as a basis for developing of econometric models for estimation of the cost of unemployment in the economy. Calculation of economic costs is very useful for policy makers as a tool for evaluation of the costs and benefits of policy measures for increasing the employability in the economy. Thus, the focus of this research is to calculate the costs of GDP form youth unemployment in North Macedonia in the period from 2010 to 2021. For that purpose, based on the MakStat database of the State Statistical Office of the Republic of North Macedonia (SSO), authors developed an econometric model to calculate the loss of GDP form youth unemployment. From the obtained results, costs from total unemployment are on average 1.62% from potential GDP over the period 2010-2020, while the costs from youth unemployment varies from 0.57% in 2011 to 0.14% in 2020. Also, authors discuss results and give some recommendations for overcoming the challenges of high youth unemployment
Keywords: youth unemployment, economic growth, Okun’s law, growth rates, youth unemployment rates